2018
DOI: 10.1371/journal.ppat.1007348
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcal Lancefield polysaccharides are critical cell wall determinants for human Group IIA secreted phospholipase A2 to exert its bactericidal effects

Abstract: Human Group IIA secreted phospholipase A2 (hGIIA) is an acute phase protein with bactericidal activity against Gram-positive bacteria. Infection models in hGIIA transgenic mice have suggested the importance of hGIIA as an innate defense mechanism against the human pathogens Group A Streptococcus (GAS) and Group B Streptococcus (GBS). Compared to other Gram-positive bacteria, GAS is remarkably resistant to hGIIA activity. To identify GAS resistance mechanisms, we exposed a highly saturated GAS M1 transposon lib… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 85 publications
0
16
0
Order By: Relevance
“…Recent structural examinations and composition analysis of the GAC also suggest the presence of glycerol phosphate (GroP) (18), an observation that remained unnoticed for over 50 years (19, 20). Further, Edgar et al (18) demonstrated that ∼25% of GAC side-chain GlcNAcs are decorated with GroP, imparting a negative charge to this polymer that has implications for S. pyogenes biology and defense mechanisms (19, 21). This feature, previously identified in other surface glycans (22, 23), provided new insight into the structural composition, biosynthesis, and function of GAC.…”
Section: Introductionmentioning
confidence: 99%
“…Recent structural examinations and composition analysis of the GAC also suggest the presence of glycerol phosphate (GroP) (18), an observation that remained unnoticed for over 50 years (19, 20). Further, Edgar et al (18) demonstrated that ∼25% of GAC side-chain GlcNAcs are decorated with GroP, imparting a negative charge to this polymer that has implications for S. pyogenes biology and defense mechanisms (19, 21). This feature, previously identified in other surface glycans (22, 23), provided new insight into the structural composition, biosynthesis, and function of GAC.…”
Section: Introductionmentioning
confidence: 99%
“…To reach the plasma membrane, AMPs have to traverse the Gram-positive cell envelope. There is substantial evidence that changes in the net charge of cell envelope components, peptidoglycan and teichoic acids, modulate the resistance of bacteria to AMPs 63 , 66 , 72 75 . We previously demonstrated that modification of GAC and the S. mutans rhamnopolysaccharide with negatively charged GroP moieties renders GAS and S. mutans more sensitive to hGIIA activity 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Aliquots were thawed and diluted to 1:1000 in HEPES buffer solution. The susceptibility experiments were performed as described previously 75 . Briefly, the AMP (hGIIA, lysozyme, and histone mixture) was serially diluted in HEPES solution.…”
Section: Methodsmentioning
confidence: 99%
“…Lancefield grouping is the traditional method which subdivides Streptococcus genus into 20 groups based on the presence of polysaccharides and teichoic acid antigens on the cell wall ( Slater, 2007 ; Efstratiou et al, 2017 ). Among the groups, both group A Streptococcus (GAS) and group B Streptococcus (GBS) are the most prevalent human pathogens that cause systemic infections associated with high mortality and morbidity ( van Hensbergen et al, 2018 ). Streptococcus pyogenes , which is a GAS bacterium, infects at least 700 million individuals each year, with a mortality rate of 15–30%, resulting in meningitis, toxic shock syndrome, and pharyngitis ( Zorzoli et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%